Implementasi dan Dampak Kurikulum Merdeka dalam Pembelajaran Pendidikan Agama Islam di Sekolah Islam Manu Putra Buntet Pesantren (Aktivisme: Jurnal Ilmu Pendidikan, Politik dan Sosial Indonesia, 2025)
The Merdeka Curriculum is a curriculum designed to provide flexibility to educational units in developing student-centered learning, including in Islamic Religious Education (PAI) subjects. This research aims to describe the implementation of the Merdeka Curriculum and analyze its impact on PAI learning at Manu Putra Buntet Pesantren Islamic School. This research uses a descriptive qualitative method with data collection techniques in the form of observation and interviews with the school's Vice Principal for Curriculum. The results show that the Merdeka Curriculum has been implemented in grades X and XI, while grade XII still uses the 2013 Curriculum due to an unfinished transition process. In its implementation, this curriculum strives to encourage student activity and integrate Islamic values according to the characteristics of the pesantren (Islamic boarding school) environment. However, students' adaptation to the active learning model is not yet optimal, so learning still tends to be teacher-centered. In addition, limitations in facilities and infrastructure such as projectors and technological devices also hinder the full implementation of innovative methods. Overall, the Merdeka Curriculum has a positive impact on strengthening religious character and contextualizing PAI learning but requires improved facilities and further mentoring for teachers and students so that the curriculum's goals can be optimally achieved.